Pengaruh Model Pembelajaran Example Non Example Terhadap Hasil Belajar Kognitif IPA Siswa Kelas V Sekolah Dasar - Lestari, Meri; Hetilaniar, Hetilaniar; Dirgantara, Marvinda Rizki Dita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the effect of the part and whole method on the long jump learning This study aims to determine whether the Non-Example Example Learning Model can improve Science Learning Outcomes of Class V Students at State Elementary School 195 Palembang. This research is a type of quantitative research using experimental methods, the type of research is True Experimental, PosttestOnly Design. The variables of this study consisted of the independent variable (X), namely the ExampleNon Example Learning Model and the dependent variable (Y) Learning Outcomes. The population in this study were all fifth grade students of SD Negeri 195 Palembang, totaling 131 people. The sampling technique used is the Simple Random Sampling technique. Data collection techniques in this study were tests and observations. The data obtained were then calculated using the SPSS.22 application. Validation of the test instrument was tested using the Product Moment correlation formula and the Reliability Test using Split-Half. The data analysis technique used the t test, which was carried out after knowing the normality and homogeneity tests. The experimental class that was given treatment with the example non example learning model obtained a posttest average of 84,688 and the control class obtained an average posttest of 60.36. With the hypothesis testing criteria, Ha is accepted if tcount > ttable with the acquisition of tcount 7,199 and ttable 2,002 then Ha received. The results of this study indicate that there is a significant effect between the non-example exampel learning model on the science learning outcomes of fifth graders at State 195 Palembang.